E-HRM IN AN E-BUSINESS ENVIRONMENT - Sharma, Megha (IJRDO -Journal of Computer Science Engineering, 2015)
This special issue on Electronic Human Resources Management (E-HRM) in an E-Business environment looks t opportunities and challenges associated with recruiting and developing firm’s workforce in a digital world characterized by endemic talent scarcity, changing values and shifting on- and offline behaviours of candidates and employees. We first draw on a Delphi study with leading HR executives from 25 internationally renowned large firms and on a quantitative survey with 144 HR managers from German top 1,000 firms to delineate the key trends and issues for modern HR executives. Demographic challenges and the war for talent are seen as the most important trends in firms of all sizes and in all industries, even ahead of, for example, social media or the global economic crisis. Resulting from these trends, our survey reveals that HR managers‟ most pressing challenges are staff retention and internal and external employer branding. Overall, the results emphasize the importance for an E-HRM that needs to be both effective – adequately fill vacancies – and efficient – make best use of scarce resources. The papers in the special issue address some of the open issues identified. Overall, in a peer-review process two out of nine submitted articles were selected for the special issue (22 per cent acceptance). The first paper by Stefan Strohmeier scrutinizes how e-portfolios can improve e-recruiting and talent management. The second paper by Sharna Wiblen, David Grant and Kristine Dery uses a single case study to learn how a shift from HRM to E-HRM can affect talent management and people in n organization nd transform firm’s IT and HR function